Strategi Perseroan Terbatas dalam Menghadapi Tantangan Pasar Modal Global Ditinjau dari Hukum Perusahaan dan Prinsip Transparansi - Angelina Sidiprasetija; Celia Angelyn Coandi (CV Rewang Rencang, 2025)
The strategy of limited liability companies (PTs) in facing the challenges of the global capital market includes various important approaches. First, increasing transparency and implementing good corporate governance (GCG) to attract investor confidence. Second, diversify products and markets as a risk mitigation measure. Third, utilize technology and innovation to improve efficiency and competitiveness. Fourth, comply with international regulations to avoid legal issues. In addition, HEIs need to strengthen international networks and adapt to global market dynamics, in order to maintain a competitive position and expand opportunities in an increasingly complex and globally connected capital market.